Android-Based Physical Fitness Assessment Application for Student of Senior High School 1 Kudus - supriyadi, hery; Rustiadi, Tri; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The purpose of this study is producing an android application product which makes it easier for physical education teachers and students to measure physical fitness. The problems of the study are 1). What is the android-based physical fitness assessment application for students of Senior High School 1 Kudus’ model? 2). How effective is the android-based physical fitness assessment application for students of Senior High School 1 Kudus?The results of this study is an android-based application product of physical fitness test for students of Senior High School 1 Kudus which is effective and attractive to use by both physical education teachers and students. The validation result by material experts in all aspect is